2022
DOI: 10.1007/s10461-022-03817-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Injectable Therapy for People with HIV: Looking Ahead with Lessons from Psychiatry and Addiction Medicine

Abstract: Long-acting injectable antiretroviral medications are new to HIV treatment. People with HIV may benefit from a treatment option that better aligns with their preferences, but could also face new challenges and barriers. Authors from the fields of HIV, substance use treatment, and mental health collaborated on this commentary on the issues surrounding equitable implementation and uptake of LAI ART by drawing lessons from all three fields. We employ a socio-ecological framework beginning at the policy level and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 112 publications
0
1
0
Order By: Relevance
“…Insurance coverage for LAI is limited and insurers may institute cost-containment conditions, including requirements for prior authorization, patient cost sharing, step therapy, and formulary exclusions that can further impede LAI prescribing [ 25 ]. The only option for many PLWH to access treatment is through the Ryan White HIV/AIDS program [ 26 ]. One study found that financial coverage for LAI and staffing challenges caused barriers to LAI administration at Ryan White–funded HIV clinics [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insurance coverage for LAI is limited and insurers may institute cost-containment conditions, including requirements for prior authorization, patient cost sharing, step therapy, and formulary exclusions that can further impede LAI prescribing [ 25 ]. The only option for many PLWH to access treatment is through the Ryan White HIV/AIDS program [ 26 ]. One study found that financial coverage for LAI and staffing challenges caused barriers to LAI administration at Ryan White–funded HIV clinics [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic psychotic disorders may be prescribed LAI-antipsychotic medications that are prescribed by psychiatrists and administered in outpatient psychiatric care settings. 55 LAI-antipsychotics have been shown to improve medication adherence and lower relapse rates in psychiatric practice. [56][57][58] Co-location of services for administering LAI-PrEP and psychotropic medications may be a promising model to make HIV prevention more accessible.…”
Section: Discussionmentioning
confidence: 99%
“…14,18 A similar model may also be amenable to adaptation to substance use treatment facilities where LAI anticraving medications like buprenorphine and naltrexone are administered. 55 This clinical infrastructure (e.g.,. refrigerated storage, dedicated staff, and patient panel tracking) is more likely to be pre-existing in psychiatric clinical contexts as compared with primary care settings, 55 where FM physicians are more likely to work, which may help explain the finding that psychiatry residents were more likely to recommend LAI-PrEP than FM residents for the SCZ-LAI condition.…”
Section: Discussionmentioning
confidence: 99%
“…As of 2021, CAB/RPV is the first long-acting injectable antiretroviral therapy authorized for use in HIV patients who are treatment-naive or experienced [99,226]. Moreover, there has been a notable surge in research on the creation of long-acting pharmacological formulations for people diagnosed with HIV [104,227]. In addition to CAB/RPV, research focuses on alternative long-acting injectables, including long-active capsid inhibitors and long-acting slow-effective release antiretroviral therapy (LASER ART).…”
Section: Challenges and Opportunities In Overcoming Hiv Drug Resistancementioning
confidence: 99%